Effect of nitrogen and potassium on oil yield, nutrient uptake and soil fertility in soybean (Glycine max)- sesame (fiesamum indicum) intercropping system* - MONDAL, S S; PRAMANIK, C K; DAS, J (The Indian Journal of Agricultural Sciences, 2014)
Â Â Â